IMPACT ASSESSMENT OF JYS PROJECT ON FIVE VILLAGES - MR. P.A. VEDPATHAK; PROF. P.A. HANGARGEKAR (International Journal of Innovations in Engineering Research and Technology, 2021)
In the state of Maharashtra, inconsistency of rains in the very times of crop growth and discontinuity of rains create drought-like situation and agriculture field is heavily impacted. Considering irrigation facilities in the state, factors mainly challenging development of state are -limited irrigation facility (according to report of water and irrigation committee, even if entire irrigation capacity is utilized, 44% area will remain dryland), large coverage of drought-prone area (159 Lacs Hectare which means 52% of cultivable area), large proportion of poor and downgraded land (42.20%), increasing uncertainty in the agricultural field due to uneven, unpredictable, and intermittent rainfall. To permanently overcome drought situation, Jalyukta Gaav (waterfull village) campaign was implemented in 5 districts from Pune division in the year 2012-13.Under this, action plan was prepared for water harvesting and increasing groundwater level by implementing various schemes collectively through coordination of all departments. Through all these projects, decentralized water storage of 8.40 TMC capacity has been created. Because of this, groundwater level is increased by 1 to 3 Meter and provision for drinking water and protected irrigation for farming is made.